2017
DOI: 10.2298/ciceq150711005z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of DME by CO2 hydrogenation over La2O3-modified CuO-ZnO-ZrO2/HZSM-5 catalysts

Abstract: Article Highlights • La-modified CuO-ZnO-ZrO2/HZSM-5 catalysts were prepared by an oxalate co-precipitation method • La-modified CuO-ZnO-ZrO2/HZSM-5 catalysts show higher catalytic performances • The catalytic performances of the catalysts are strongly dependent on the La content

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…435,551 Accordingly, La 2 O 3 -modified CuO–ZnO–ZrO 2 /HZSM-5 catalysts were prepared by an oxalate co-precipitation method for DME direct synthesis (Table 5, entry 29). 552 A suitable amount of La 2 O 3 improved the catalytic performance of CuO–ZnO–ZrO 2 /HZSM-5, and maximum 34.3% CO 2 conversion and 57.3 and 19.6% DME selectivity and yield were obtained over the catalyst with 1% La 2 O 3 at 270 °C and 3 MPa. The addition of La 2 O 3 modified the population and strength of acid sites as well as the dispersion of Cu and reducibility of CuO with a larger Cu + /Cu ratio.…”
Section: Catalytic Conversion Of Co2mentioning
confidence: 89%
“…435,551 Accordingly, La 2 O 3 -modified CuO–ZnO–ZrO 2 /HZSM-5 catalysts were prepared by an oxalate co-precipitation method for DME direct synthesis (Table 5, entry 29). 552 A suitable amount of La 2 O 3 improved the catalytic performance of CuO–ZnO–ZrO 2 /HZSM-5, and maximum 34.3% CO 2 conversion and 57.3 and 19.6% DME selectivity and yield were obtained over the catalyst with 1% La 2 O 3 at 270 °C and 3 MPa. The addition of La 2 O 3 modified the population and strength of acid sites as well as the dispersion of Cu and reducibility of CuO with a larger Cu + /Cu ratio.…”
Section: Catalytic Conversion Of Co2mentioning
confidence: 89%
“…Considering the previous study of Guo et al [140] on the effect of La doping on Cu/ZrO 2 catalysts, this enhancement is associated with an increase in the amount of basic sites that enhance the adsorption of CO 2 and the selectivity toward methanol formation [140]. The best CO 2 conversion (34.3%) and selectivity toward DME (57.3%) was achieved with the catalyst modified with 1% La 2 O 3 , which was linked to the optimization of the adsorption of CO 2 and the formation of the smaller Cu active species [139].…”
Section: Precipitationmentioning
confidence: 94%
“…Recently, Zhang et al [139] studied CuO-ZnO-ZrO 2 /HZSM-5 hybrids modified with La 2 O 3 prepared by co-precipitation. It was found that the catalyst modification with La 2 O 3 enhanced its performance in direct CO 2 hydrogenation to DME (270 • C and 30 MPa).…”
Section: Precipitationmentioning
confidence: 99%
“…The CO 2 conversion as well as the selectivity toward CO, CH 3 OH and DME are calculated by internal standard method. 32,33 X CO 2 , S P i and Y DME represent the conversion of CO 2 , the selectivity of the product (DME, MeOH, CO) and the yield of DME, respectively. Each experimental data was corresponds to an average of three independent measurements, with error of ±2%.…”
Section: Methodsmentioning
confidence: 99%